2007
DOI: 10.1085/jgp.200709774
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Demonstration of Closed-State Inactivation of K+ Channels at Low pH

Abstract: Lowering external pH reduces peak current and enhances current decay in Kv and Shaker-IR channels. Using voltage-clamp fluorimetry we directly determined the fate of Shaker-IR channels at low pH by measuring fluorescence emission from tetramethylrhodamine-5-maleimide attached to substituted cysteine residues in the voltage sensor domain (M356C to R362C) or S5-P linker (S424C). One aspect of the distal S3-S4 linker α-helix (A359C and R362C) reported a pH-induced acceleration of the slow phase of fluorescence qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 46 publications
(124 reference statements)
6
44
0
Order By: Relevance
“…In other Kv channels, such as Shaker, Kv1.4, and Kv1.5, maximal conductance is reduced at low pH as a result of stabilization of channels in inactivated states (7,9,11,31,42,53). In hERG channels there is evidence that a similar inactivation mechanism occurs (47)(48)(49)51), and so the possibility that low pH reduces maximal conductance by stabilizing hERG channels in the inactivated state was explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other Kv channels, such as Shaker, Kv1.4, and Kv1.5, maximal conductance is reduced at low pH as a result of stabilization of channels in inactivated states (7,9,11,31,42,53). In hERG channels there is evidence that a similar inactivation mechanism occurs (47)(48)(49)51), and so the possibility that low pH reduces maximal conductance by stabilizing hERG channels in the inactivated state was explored.…”
Section: Resultsmentioning
confidence: 99%
“…A similar mechanism has been proposed in Kv1.5 channels, where titration of a histidine residue in the turret region is responsible for inducing inactivation from both open and closed states, resulting in a reduction of maximal conductance at low pH (8,31,53). It has also been suggested that protons stabilize both open and closed inactivated states in Shaker channels, resulting in a reduction in maximal conductance (11,35). hERG channels have five native histidines that may be accessible to the extracellular solution ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The VCF technique was first used to gain insights into the structural rearrangements of Shaker K + voltage‐gated channels by the Isacoff laboratory 30 . It has since provided a wealth of information on potassium channels, especially on movements of the voltage sensor and its neighbouring domains 20,21,30–37 . It was subsequently applied to various other membrane proteins, including hyperpolarization‐activated cyclic nucleotide‐gated channels, 38,39 sodium channels, 22,40–42 Na + /K + ‐ATPase, 43,44 Na + Pi cotransporter 45,46 and glutamate transporters 47,48 .…”
Section: Voltage Clamp Fluorometry Of Lgicsmentioning
confidence: 99%
“…30 It has since provided a wealth of information on potassium channels, especially on movements of the voltage sensor and its neighbouring domains. 20,21,[30][31][32][33][34][35][36][37] It was subsequently applied to various other membrane proteins, including hyperpolarizationactivated cyclic nucleotide-gated channels, 38,39 sodium channels, 22,[40][41][42] Na + /K + -ATPase, 43,44 Na + Pi cotransporter 45,46 and glutamate transporters. 47,48 The work on voltage-gated ion channels has been reviewed extensively elsewhere.…”
Section: Voltage Clamp Fluorometry Of Lgicsmentioning
confidence: 99%
“…It should be considered that these crystal structures and our present computational model (biased to a closed-inactivated conformation) were obtained with the channel inner gate (TM2) in its closed conformation. Still, the presence of a closed-inactivated state at the functional level in Shaker (Baukrowitz and Yellen, 1995;Claydon et al, 2007;Panyi and Deutsch, 2006) supports the structural basis of an inactivated state even when the lower gate in closed. Given the stability of the inactivated conformation of the filter induced by the His71-Asp80 interaction in E71H, this mutant remains a viable candidate for the structure of a closed-inactivated form of the filter.…”
Section: 44 Engineering Hydrogen-bond Network In Kv Potassium Channelsmentioning
confidence: 80%